Sustainability in the textile sector through industry 4.0: A lifecycle-based qualitative study - Iker Laskurain-Iturbe; Germán Arana-Landín; Cristina Peña-Rodriguez; Amaia Mendoza; Beñat Landeta-Manzano; Naiara Uriarte-Gallastegi (International Journal of Production Management and Engineering)
The textile industry is among the most polluting sectors globally, primarily due to the rise of fast fashion and limited recycling practices. Addressing this challenge requires transformative approaches, among which Industry 4.0 technologies stand out as promising tools. This paper presents the findings of a qualitative study based on 16 in-depth interviews with key stakeholders in the Spanish textile sector. The research explores the potential of these technologies to enhance sustainability across various stages of the textile product life cycle. The results indicate that Industry 4.0 technologies can significantly contribute to improving environmental, economic, and social sustainability in the sector. However, further research is needed to identify the most impactful applications and to support their adoption, particularly among small and medium-sized enterprises.